DYNAMICS OF UKRAINE'S ECONOMIC DEVELOPMENT AND ECONOMIC GROWTH MODELS - Holovynova, H. M. (Science and Transport Progress, 2006)
In article considers topical issues of the quality of economic growth. In modern conditions the processes of economic development require passing from extensive levers of reforming economy and state regulation to intensive ones, which would stimulate private initiative and investments.